THE IMPACT OF EARNINGS MANAGEMENT ON CAPITAL ADEQUACY: AN APPLIED STUDY OF A SAMPLE OF BANKS LISTED IN THE IRAQI STOCK EXCHANGE - Saeb Salim Mohammed; Ahmed Jasim Hameed (Scholar Express Journals, 2023)
The research aims to show the effect of real earnings management on capital adequacy for a sample of banks listed in the Iraq Stock Exchange. The research sample consisted (10) banks listed in the Iraq Stock Exchange for the period from 2010 to 2019, as real earnings management was measured through the provision for loan losses, unusual cash flows, and estimated expenses, and capital adequacy was measured through the basic and additional capital divided by risk weighted assets. The research concluded that there is an adverse effect of real earnings management practices on capital adequacy, and the research recommends the need for banks to comply with Basel requirements because of their role reduce earnings management practices.
Keywords: Earnings Management; Capital Adequacy